Advances in organic synthesis. - Rahman, Atta-ur-, 1942- (Bentham Science Publishers, 2013)
Modern Organofluorine Chemistry-Synthetic Aspects - The volume focuses on recent advances in organofluorine chemistry directed towards selective fluorine introduction into various target molecules, employing both traditional and contemporary, electrophilic and nucleophilic, fluorinating agents. It brings together sixteen chapters written by leading experts and active researchers in the field. It is an excellent source of information for synthetic chemists interested in selective fluorination methods and fluorinated building blocks. Advances in Organic Synthesis is a book series devoted to publ.